2020
DOI: 10.1371/journal.pone.0240116
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the effect of different disinfectants on the biofilm of Staphylococcus epidermidis and Staphylococcus aureus formed on acrylic ocular prostheses

Abstract: The aim of this study was to evaluate the effect of disinfectants on the biofilm of Staphylococcus aureus and Staphylococcus epidermidis formed on the acrylic surface of ocular prostheses. In this study, 396 acrylic specimens were manufactured (50% for Staphylococcus epidermidis, and 50% for Staphylococcus aureus). For each bacterium, 66 specimens were subjected to biofilm formation on their surfaces for 24 hours, 66 specimens were subjected to biofilm formation on their surfaces for 48 hours, and 66 specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Earlier studies on biofilm formation in ocular isolates of S. aureus and S. epidermidis were done using synthetic material such as silicone, polymethyl-acrylate, hydrophilic acrylic, hydrophobic acrylic, etc. [ 25 , 62 , 63 , 90 ], to understand their biofilm formation ability on indwelling devices including contact lenses, sutures, scleral buckles, valvular tubes and keratoprostheses [ 20 , 24 , 25 , 26 , 52 , 77 , 91 , 92 , 93 ]. In our opinion, monitoring biofilm formation of ocular fluid S. aureus and S. epidermidis on cadaveric cornea is equally important because they are a major source of hospital-acquired infections and more importantly, corneal biofilms have been reported following experimental keratitis in mice [ 77 ], in patients with infectious crystalline keratopathy [ 94 , 95 , 96 ] or pterygium scleritis [ 97 ] and also in the absence of prosthetic material and in the absence of active corneal inflammation or infection [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies on biofilm formation in ocular isolates of S. aureus and S. epidermidis were done using synthetic material such as silicone, polymethyl-acrylate, hydrophilic acrylic, hydrophobic acrylic, etc. [ 25 , 62 , 63 , 90 ], to understand their biofilm formation ability on indwelling devices including contact lenses, sutures, scleral buckles, valvular tubes and keratoprostheses [ 20 , 24 , 25 , 26 , 52 , 77 , 91 , 92 , 93 ]. In our opinion, monitoring biofilm formation of ocular fluid S. aureus and S. epidermidis on cadaveric cornea is equally important because they are a major source of hospital-acquired infections and more importantly, corneal biofilms have been reported following experimental keratitis in mice [ 77 ], in patients with infectious crystalline keratopathy [ 94 , 95 , 96 ] or pterygium scleritis [ 97 ] and also in the absence of prosthetic material and in the absence of active corneal inflammation or infection [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus and S. epidermidis are also the leading cause of infection of ocular implants such as intra-ocular lenses, Scleral buckles, Conjunctival plug, Lacrimal intubation devices, etc. [ 21 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…and S. aureus) on them. [11][12][13][14][15] Patients evaluated in this study slept with their dentures removable. Individuals who sleep with their dentures removable tend to have poor oral hygiene practices, high rates of microbial plaque on their tongues and dentures, oral candidiasis, and visit their dentists less often.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical immersion technique is essentially the method of choice for the cleaning of maxillofacial prostheses by careful rubbing of their internal surface (Filié Haddad et al, 2011;Guiotti et al, 2016;Paranhos et al, 2007). Although the chlorhexidine gluconate (CHX) solution has been widely employed as an antimicrobial disinfectant (de Azevedo et al, 2021;Filié Haddad et al, 2011;Guiotti et al, 2016;Miranda et al, 2019;Moreno et al, 2020), possible structural damage to biomaterials has been observed with its use, such as roughness and microhardness as the main altered physical and mechanical properties of maxillofacial silicone elastomers (Moreno et al, 2013); however, divergent results have been reported elsewhere (Chamaria et al, 2019). In addition, Daro Brand® is a commercial antibacterial product used as an alternative for cleaning maxillofacial prostheses, but no studies have proved its effects as a disinfectant.…”
Section: Introductionmentioning
confidence: 99%